2019
DOI: 10.1016/j.jsps.2019.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of GRM4, SCN2A and SCN3B polymorphisms on antiepileptic drugs responsiveness and epilepsy susceptibility

Abstract: BackgroundPharmacotherapy of epilepsy including antiepileptic drugs (AEDs) is one of the main treatment approaches. As a biological target, sodium channels (Nav channels) and glutamate receptor genes are playing a major role in the etiology and treatment of epilepsy.ObjectiveThis study aims to investigate the genetic associations of certain genetic polymorphisms with increased risk of epilepsy susceptibility and variability in response to AEDs treatment in a Jordanian Arab population.MethodA pharmacogenetics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Nav channels are the main targets of many first-line AEDs ( 31 34 ). SCN1A and SCN2A genetic variants may change the response to AEDs ( 25 ). SCN1A rs2298771 (c.3184A>G/p.Thr1067Ala), located in the SCN1A exon region, is an A-to-G variant, which causes the substitution of alanine for threonine ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nav channels are the main targets of many first-line AEDs ( 31 34 ). SCN1A and SCN2A genetic variants may change the response to AEDs ( 25 ). SCN1A rs2298771 (c.3184A>G/p.Thr1067Ala), located in the SCN1A exon region, is an A-to-G variant, which causes the substitution of alanine for threonine ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Shi et al ( 5 ) found that the rs2304016 G allele increased the risk of VPA resistance. Moreover, some studies have shown that the rs2304016 polymorphism does not affect the risk of AED resistance ( 7 , 10 , 14 , 21 – 23 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, this study encountered some limitations such as small sample size and focusing on genotyping certain polymorphisms. Moreover, only a few pharmacogenetic studies [33][34][35][36][37][38][39][40][41][42][43][44] have been conducted in Jordan. Therefore, more studies are recommended in this topic by investigating other VIP variants in different candidate genes.…”
Section: Discussionmentioning
confidence: 99%
“…Genome wide association studies (GWAS), immunohistochemical, and pharmacologic studies strongly suggest a role for mGlu4 in epilepsy, and the GRM4 gene (human chromosome 6, band p21.3) resides within a known susceptibility locus known for juvenile myoclonic epilepsy 300,363 . GWAS analysis has discovered a moderate but significant association of the GRM4 SNP, rs2029461, with both generalized 364 and juvenile myoclonic epilepsy [365][366][367] . An additional SNP, rs2451334, is significantly associated with response to anti-epileptic drugs (AEDs), underscoring the importance of mGlu4 in epilepsy treatment 364 .…”
Section: Epilepsymentioning
confidence: 99%